Influence of donor sex and age on graft outcome in kidney transplantation - Melk, Anette; Sugianto, Rizky I; Zhang, Xun; Dahhou, Mourad; Döhler, Bernd; Süsal, Caner; Sapir-Pichhadze, Ruth; Wong, Germaine; Foster, Bethany J (Nephrology, dialysis, transplantation, 2024)
There is a known recipient sex-dependent association between donor sex and kidney transplant survival. We hypothesized that donor age also modifies the association between donor sex and graft survival.First, deceased donor kidney transplant recipients (1988-2019, n = 461 364) recorded in the Scientific Registry of Transplant Recipients, the Australia and New Zealand Dialysis and Transplant Registry and the Collaborative Transplant Study were analyzed. We used multivariable Cox regression models to estimate the association between donor sex and death censored graft loss, accounting for the modifying effects of recipient sex and donor age; donor age was categorized as 5-19, 20-34, 35-49, 50-59 and ≥60 years. Results from cohort-specific Cox models were combined using individual patient data meta-analysis.Among female recipients of donors aged <60 years, graft loss hazards did not differ by donor sex; recipients of female donors ≥60 years showed significantly lower graft loss hazards than recipients of male donors of the same age [combined adjusted hazard ratio (aHR) 0.90, 95% CI 0.86-0.94]. Among male recipients, female donors aged <50 years were associated with significantly higher graft loss hazards than same-aged male donors (5-19 years: aHR 1.11, 95% CI 1.02-1.21; 20-34 years: aHR 1.08, 95% CI 1.02-1.15; 35-49 years: aHR 1.07, 95% CI 1.04-1.10). There were no significant differences in graft loss by donor sex among male recipients of donors aged ≥50 years.Donor age modifies the association between donor sex and graft survival. Older female donors were associated with similar or lower hazards of graft failure than older male donors in both male and female recipients, suggesting a better functional reserve of older female donor kidneys.